Manifestations of the passion of strife in the complete fictional works of the writer Dhikra Lu'aybi - Kawthar Ashour Abdul Hussein / Khaled Mohammed Saleh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
In this research paper, our aim was to explore the manifestations of the passion of strife  and their application to " the complete fictional works of the writer Dhikra Lu'aybi". We sought to identify the lexical and semantic manifestations that emerged within the narrative texts by delving into the psychological and physical levels of the addressed characters. By examining their psychological, emotional, and sensory states through distinct semantic and lexical manifestations, we aimed to uncover the manifestations of both the ideological and semantic dimensions of the characters. Semiotics of inclinations played a crucial role in unraveling the prominent logical interpretations shaping the text.